Putrajaya ou une utopie malaisienne. Projet urbain et défi politique - Frédéric Bouchon (Bulletin de l’Association de Géographes Français)
Building a new capital city is the founding basis or the expression of a major shift in a nation shaping. Putrajaya project in Malaysia was inspired after post-colonial urban models such as Brasilia and Chandigarh. It aimed to embody spatially the vision of the future Malaysian society. It was designed to be breaking with Kuala Lumpur’s chaotic morphology and mixed essence. It is a satellite city with ambitious urban and technological transformation project. This Federal capital city presents a monumental modernist morphology with Muslim-Malay-inspired aesthetics. Twenty years after the site selection, more than hundred thousand people live in the city. Building and transfering Federal Government departments was fast and smooth due to the location of the new town in the metropolitan area of Kuala Lumpur. Yet, some urban planning decisions remain controversial; described as in opposition to the multicultural spirit of the nation, or a misuse of the national oil rent. Research on Putrajaya have focused on its architecture and town planning issues, with few studies on the urban space representation from users. The lack of synthesis on this new city, its ambitions, dynamics and its role as capital city explains this research project. This qualitative research is a case study, based on analysis of secondary data, observations and interviews with urban actors. It appears that Putrajaya is both a project of rupture, due to its sheer size, but it is also in continuation of public development policies in place since Malaysian independence. The project of administrative deconcentration in a monumental setting fits so as a continuum of a social model in place.